Averaging of Systems with Slow Variables - Efendiev, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We justify the averaging method for systems with delay described by both “slow” and “fast” variables. The results obtained are applied to the analysis of one problem in control theory.